第50次日本南極地域観測隊気象部門報告2009 - 菅谷, 重平; スガヤ, ジュウヘイ; 土井, ひかる; ドイ, ヒカル; 辰己, 弘; タツミ, ヒロシ; 伊藤, 智志; イトウ, サトシ; 小森, 智秀; コモリ, トモヒデ; Sugaya, Juhei; Doi, Hikaru; et al. (2014)
P(論文) この報告は，第50次日本南極地域観測隊気象部門が2009年2月1日から2010年1 月31日まで昭和基地において行った気象観測結果をまとめたものである．観測方法・測器・統計方法等は第49次隊とほぼ同様である． 越冬期間中の特記事項は次のとおりである． 1）2009年のブリザード回数は29回で平年並みだったが，そのうちのA級（最大階級）ブリザードは，1978年と並ぶ13回と最多回数を記録した． 2）2 月21 日に，観測史上最大である日最大風速47.4 m/s を記録した． 3）昭和基地上空の対流圏において，月平均気温は5-7 月にかけて高く推移した． 一方，下部成層圏では8-10 月にかけて平年より低かった． 4）昭和基地上空のオゾン全量は，8月中旬から10月下旬までオゾンホールの目安となる220 m atm-cm をほぼ継続して下回り，10月には2009 年の最小値である135m atm-cm を記録したが，11月には昭和基地上空がオゾンホールから抜けたためオゾン全量が一気に増加した． This report describes the results of meteorological observations carried out by the Meteorological Observation Team of the 50th Japanese Antarctic Research Expedition (JARE-50) at Syowa Station from February 2009 to January 2010. The observation methods, instruments, and statistical methods used by JARE-50 were similar to those used by JARE-49. The most notable results are as follows. 1) Class-A blizzards, the heaviest storm class, were recorded 13 times. This frequency is the same as in 1978, which was the highest on record. A total of 29 blizzards (of various classes) occurred in 2009, which is close to normal. 2) The maximum sustained wind speed of 47.4 m/s was recorded on 21 February 2009. 3) Tropospheric temperatures for May-July over Syowa Station were higher than normal, but temperatures in the lower stratosphere for August-October were lower than normal. 4) Total ozone over Syowa Station was less than 220 m atm-cm between the middle of August and the end of October. The minimum value in 2009 was 135 m atm-cm. Total ozone increased rapidly in November 2009 when the ozone-hole area decreased around Syowa Station. departmental bulletin paper